Description of healthy house status based on the physical condition of community houses in Sama Subur Village, North Konawe - Hartati Bahar; Paridah Paridah; Afifa Yunizah (Indonesian Journal of Health Science, 2026)
A healthy home is an important factor in public health because the physical condition of the house greatly affects the comfort and health of the people who live in it. This study aims to explain the ownership status of healthy homes based on the physical condition of the building in Sama Subur Village, Motui District, North Konawe Regency. The research method used is a descriptive design with a quantitative approach. The population studied were all heads of families who actively live in Sama Subur Village, with a sample of 45 heads of families selected through a total sampling technique. Data were collected by conducting interviews using a prepared questionnaire and observing the physical condition of the house which includes the building area, type of floor, walls, roof, ceiling, lighting, temperature, ventilation, use of windows, and the condition of the environment around the house. The data analysis process was carried out descriptively by presenting frequency distribution and percentages. The results of this study indicate that the majority of respondents' homes fall into the category that does not meet the requirements for a healthy home, amounting to 55.6%, while only 44.4% meet the requirements. Although most of the physical indicators of the house, such as waterproof floors (80.0%), tightly closed walls (80.0%), waterproof roofs (84.4%), adequate lighting (91.1%), and available ventilation (86.7%) have been met, there are still several deficiencies in the building area, completeness of the house structure, and cleanliness of the environment around the house. The conclusion of this study indicates that the implementation of healthy homes in Sama Subur Village has not reached an optimal level and requires special attention through increased education for the community and support from various sectors to improve the physical quality of houses and the living environment.